Appropriateness analysis of implementing a smart grid system in campus buildings using the fuzzy method - Dina Maizana; Syarifah Muthia Putri (Institute of Advanced Engineering and Science, 2022)
The smart building campus is still being studied by researchers until now. Given the importance of meeting key performance indicators on smart campuses. Medan Area University is a campus that uses a smart grid system to solve energy management problems. With the position of the Medan Area University being in an area that has the potential to utilize photovoltaic (PV) solar renewable energy sources. With the designation of Google Earth data, the average sunlight intensity in the campus area is 4,528 KWh/m2. The design of the smart grid system is carried out by making solar PV solar as the main source and 4 computers as loads. The fuzzy method was chosen in the smart grid system simulation that has been designed because the fuzzy method can provide decisions in the intersection area. To facilitate analysis The MATLAB program is used to assist in the simulation. So that the output can show results that are close to real conditions. Based on 144 hours of data that has been entered into the fuzzy method, the output shows the results are appropriate to be implemented.